Structure analysis of a heteropolysaccharide from Taraxacum mongolicum Hand.-Mazz. and anticomplementary activity of its sulfated derivatives. (5th November 2016) - Chen, MiaoMiao; Wu, Jianjun; Shi, Songshan; Chen, Yonglin; Wang, Huijun; Fan, Hongwei; Wang, Shunchun
Highlights: A homogenous polysaccharide, DPSW-A, was extracted from the herb Taraxacum mongolicum Hand.-Mazz . The chemical structure of DPSW-A was determined. The sulfated derivatives of DPSW-A exhibit anticomplementary activity. The relationship of the chemical structure with the anticomplementary activity of sulfated polysaccharides was discussed. Abstract: A homogenous water-soluble polysaccharide, DPSW-A, with a deduced chemical structure was extracted from the herb Taraxacum mongolicum Hand.-Mazz . Moreover, 80.813-kDa DPSW-A is composed of three types of monosaccharide, namely rhamnose, arabinose, and galactose, at a molar ratio of 1.0:10.7:11.9. The main chain of DPSW-A contains Terminal-Gal p, 1, 3-Gal p, 1, 6-Gal p, 1, 3, 6-Gal p, and 1, 2, 4-Rha p ; the branched chain contains Terminal-Ara f, 1, 5-Ara f, and 1, 3, 5-Ara f . The sulfated derivatives prepared from DPSW-A showed inhibitory effects on complement activation through the classical pathway (CH50 : Sul-DPSW-A, 3.94 ± 0.43 μg/mL; heparin, 104.40 ± 3.82 μg/mL) and alternative pathway (AP50 : Sul-DPSW-A, 42.76 ± 0.46 μg/mL; heparin, 43.42 ± 0.22 μg/mL). Mechanism studies indicated that Sul-DPSW-A inhibited complement activation by blocking C1q, C1r, C1s, and C9, but not C2, C3, C4, and C5. In addition, Sul-DPSW-A displayed limited anticoagulant effects. These results suggest that Sul-DPSW-A prepared from DPSW-A is valuable for treating diseases caused by excessive complement system activation.